Study of Population Statistics (On The Example of Population Statistics of Uzbekistan) - Babanazarova Sevara; Sharofiddinov Jakhongir (Indonesian Journal of Innovation Studies, 2022)
This article recognizes the importance of the sectors of the economy of the Republic of Uzbekistan through the study of population statistics, the importance and role of population statistics in the development of sectors of the economy, and offers suggestions and recommendations.